The Effect of Inaccurate Electronic Component Values on The Output Frequency Characteristics of Fourth Order Butterworth Type Low-pass Filter Circuits - Sujiwa, Akbar; Maniani, Billy Sopater (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
The low-pass filter opamp circuit is an active electronic circuit used to pass low frequencies. In practice, making this circuit requires active components in the form of an operational amplifier and several passive components such as resistors and capacitors. To obtain the required passive component values, calculations are carried out according to theory, but the results of these calculations sometimes make it difficult for users to find the values ​​for the same components. Components sold on the market do not always exactly match the user's needs, so sometimes these components are replaced with components whose size is close to the calculated value. Therefore, in this research, testing was carried out regarding the effect of inaccurate component values ​​on the filter output characteristics. From the results of this research, it was found that the cut-off frequency decreased by 6.25% and that premature damping occurred at low frequencies at 100 Hz. However, overall this series of filters is still suitable for use.